Influence of Degradation Processes in Lead–Acid Batteries on the Technoeconomic Analysis of Photovoltaic Systems - Jose-Maria Delgado-Sanchez; Isidoro Lillo-Bravo (Energies, 2020)
Most technoeconomic feasibility studies of photovoltaic (PV) systems with batteries are mainly focused on the load demand, PV system profiles, total system costs, electricity price, and the remuneration rate. Nevertheless, most do not emphasise the influence degradation process such as corrosion, sulphation, stratification, active material seeding, and gassing on battery lifetime, efficiency, and capacity. In this paper, it is analysed the influence of the degradation processes in lead–acid batteries on the technoeconomic analysis of PV systems with and without battery. Results show that Net Present Value (NPV), Payback Period (PBP), and Discounted PayBack Period (DPBP) have a heavy dependence on the assumptions about the value of the battery performance parameters according to its degradation processes. Results show NPV differences in the range from −307% to 740%, PBP differences in the range from 9% to 188%, and DPBP differences in the range from 0% to 211%.